Sikap dan Keterampilan Perawat tentang Pijat Bayi di St. Luke’s Medical Center, Quezon City, Philippines - Yektiningtyastuti Yektiningtyastuti; Roberto C. Sombillo; Annabelle R. Borromeo (Politeknik Kesehatan Tanjung Karang, 2017)
One procedure of health care in newborns, which have recently been developed in some countries are the baby massage. Through several studies on infant massage, infant massage has been found to be very beneficial for babies and parents.The objective of this research was to improve the nurse’s attitudes and skills on infant massage in St. Luke's Medical Center, Quezon City, Philippines. Methodology that used to assess nurses' attitudes about baby massage was a pre and post-test, while for the skills of nurses was post-test only. The statistical analysis was used paired t-test to determine the differences of the two means (pre-test and post-test).The results showed that mean score of nurses' attitudes in infant massage pre-test was 81.18 (SD=7.38, 2), while mean score post-test was 91.18 (SD=6.84). Mean scores of nurses’s skills in infant massage (post-test) was 82.00. The paired t-test results showed that p-value (sig. 2-tailed)=0.001, there was significant differences between pre-test and post-test of nurses' attitudes in infant massage.